STRES BURDEN, COPING MECHANISM AND MINDFULNESS IN WORKING MOTHERS WHO HAVE PRE-SCHOOL AGE CHILDREN DURING COVID-19 PANDEMIC IN PADANGSARI VILLAGE, SEMARANG - Yulianti, Natalia Ratna; Dewi, Fransiska Padma; Wahyuningrum, Eka (Jurnal Perawat Indonesia, 2021)
Background: The Covid-19 pandemic requires all activities to be centered at home. During the pandemic, working women have special challenges in managing their time because of the additional role they have, namely being a teacher for their children in learning at home. This can lead to its own stress load. The emergence of a stress load will encourage the emergence of coping mechanisms. Actually, stress conditions can be minimized with mindfulness or self-attention. The purpose of this study is to describe the stress burden, coping mechanisms and mindfulness of working mothers who have pre-school age children during the Covid-19 pandemic. Methods: This study is a qualitative research using a phenomenological approach to five working mothers who have pre-school age children in Padangsari Village. Collecting data using in-depth interviews and analyzed using the Van Manen method. Results: This study resulted in three themes, namely 1. Child's behavior is confusing and mother leaves but still manages attention; 2. Mother's time is divided but there are other people who help and the mother accepts the situation; 3. The role of the mother as an educator are just be patient and share. Conclusion: Stress, coping and mindfulness are interrelated. With the same stress, each individual working mother has different coping and mindfulness. Working mothers should be able to recognize and be aware of their stress coping and mindfulness and be able to manage the stress that arises properly, so that they can accompany their children to the fullest.